Method for stator resistance measurement suitable for vector control - Akin, E.; Ertan, H.B.; Uctug, M.Y. (IEEE, 1994)
In this paper a method is introduced which can be used to predict the stator resistance of an asynchronous motor from current and voltage measurements without interrupting the controller or motor operation. This approach takes minimal microcontroller time. It is illustrated through realistic simulations that it can be successfully used for stator resistance measurement and update in field orientation schemes under both accelerating conditions and constant speed operating conditions of the motor maintaining output torque within 0.5% of the reference value even when a 10% abrupt change occurs in stator resistance of the motor. Work is in progress for implementation of the scheme.
Proceedings of the 20th International Conference on Industrial Electronics, Control and Instrumentation. Part 1 (of 3) -- 5 September 1994 through 9 September 1994 -- Bologna, Italy -- 42923
Keywords: Calculations; Digital signal processing; Electric current measurement; Electric currents; Electric drives; Electric resistance; Electric resistance measurement; Mathematical models; Speed; Stators; Torque; Leakage reactance; Rotor flux orientation; Stator fluxes; Stator resistance measurement; Vector control; Induction motors